What Drives Public Accountants To Undertake CPD? An Indonesian Study - Ayu Chairina Laksmi (The Indonesian Journal of Accounting Research, 2015)
Abstract: Continuing Professional Development or CPD represents the learning activities – either formal or informal learning activities for developing and maintaining the capabilities of professional accountants to perform competently within their professional environment. Using a qualitative approach, this study aims to add to the literature regarding CPD for accountants, especially CPD for the Indonesian Institute of Certified Public Accountants (IICPA) public accountant members by investigating CPD drivers. It is also the aim of this study to provide findings to assist the IICPA and the Indonesian Ministry of Finance to develop CPD policy and improve activities according to CPD drivers perceived by the public accountants. There were 48 public accountants interviewed in this study using a snowball sampling method. Thematic analysis and first and second cycle coding were employed to analyze the interview data. The findings of this study indicate that the policy regulatory bodies’ requirements received most agreement from the members as a CPD driver followed by lifelong learning and specialist skills. Lifelong learning received more agreements compared with specialist skills. The last driver, ethical requirements, was also considered as a CPD driver but it received less agreement compared with the other drivers investigated in this study.Abstrak: Pendidikan Profesional Berkelanjutan (PPL) mewakili kegiatan pembelajaran - baik kegiatan pembelajaran formal atau informal untuk mengembangkan dan mempertahankan kemampuan dan kompetensi akuntan profesional dalam lingkungan profesional mereka. Dengan menggunakan pendekatan kualitatif, studi ini bertujuan untuk menambah literatur tentang PPL untuk akuntan, terutama PPL untuk Ikatan Akuntan Publik Indonesia (IAPI) dengan menyelidiki drivers atau penggerak PPL. Studi ini juga bertujuan untuk memberikan temuan untuk membantu IAPI dan Kementerian Keuangan Indonesia sebagai regulator untuk mengembangkan kebijakan dan meningkatkan kegiatan PPL sesuai dengan drivers/penggerak para akuntan publik untuk melakukan PPL. Studi ini mewawancarai 48 akuntan publik dengan menggunakan metode purposive sampling. Analisis tematik dan pengkodean siklus pertama dan kedua digunakan untuk menganalisis data wawancara tersebut. Hasil temuan studi ini menunjukkan bahwa  persyaratan dari regulator mengenai PPL menjadi penggerak utama bagi para akuntan publik untuk mengikuti PPL. Selain persyaratan regulator, pembelajaran seumur hidup (lifelong learning) dan keahlian khusus (specialist skills) juga dipandang sebagai penggerak PPL bagi para akuntan publik. Pembelajaran seumur hidup menerima lebih banyak persetujuan dari partisipan penelitian ini dibandingkan dengan keahlian khusus. Untuk penggerak terakhir yaitu persyaratan etis (ethical requirements), juga dianggap sebagai penggerak PPL meskipun jumlah partisipan yang menyetujui lebih sedikit jika dibandingkan dengan penggerak-penggerak PPL lainnya yang diteliti oleh studi ini.